1987
DOI: 10.1007/bf01840373
|View full text |Cite
|
Sign up to set email alerts
|

On the existence and synthesis of multifinger positive grips

Abstract: We study the criteria under which an object can be gripped by a multifingered dexterous hand, assuming no static friction between the object and the fingers; such grips are called positive grips. We study three cases in detail: (i) the body is at equilibrium, (ii) the body is under some constant external force/torque, and (iii) the body is under a varying external force/torque. In each case we obtain tight bounds on the number of fingers needed to obtain grip.We also present efficient algorithms to synthesize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
216
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(219 citation statements)
references
References 18 publications
1
216
0
2
Order By: Relevance
“…As a practical matter, determining if an assembly with fixture set F has robust stability is no harder than seeing if the assembly is merely directionally stable. Borrowing from Mishra et al [16]'s work on form-closure, we prove the following: …”
Section: Robust Directional Stabilitymentioning
confidence: 81%
See 2 more Smart Citations
“…As a practical matter, determining if an assembly with fixture set F has robust stability is no harder than seeing if the assembly is merely directionally stable. Borrowing from Mishra et al [16]'s work on form-closure, we prove the following: …”
Section: Robust Directional Stabilitymentioning
confidence: 81%
“…While the problem of synthesizing stable grasps for a single object has received considerable attention [9,10,13,18,16,12], stabilization of multiple bodies has only recently been a topic of interest [19,14]. In the single-object case, the emphasis has been on synthesizing a robust, stable grasp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FORM CLOSURE Reuleaux (1963) first described form closure which captures the intuitive requirement of a fixture: a part is held in form closure if it can resist arbitrary fo rces and torques. Lakshminarayana (1978) showed that seven frictionless contacts are necessary to hold a three-dimensional part in form closure; Mishra, Schwartz and Sharir (1987) showed that seven frictionless contacts are also sufficient. Goldman and Tucker (1956), in a purely mathematical paper on linear algebra.…”
Section: Related Workmentioning
confidence: 99%
“…It must however, be remarked that when the object has rotational symmetry, frictionless contacts do not allow its immobilization. A detailed discussion about the number of contact points necessary for each case can be found in [3] [4].…”
Section: Introductionmentioning
confidence: 99%